Mechanism of Xylan Pyrolysis by Py-GC/MS - Wang, Shu-rong; Liang, Tao; Ru, Bin; Guo, Xiu-juan (Chemical research in Chinese universities, 2013)
In order to investigate the decomposition behavior of hemicellulose, xylan was chosen as the representative of hemicellulose to study the fast pyrolysis on the combination system of analytical pyrolyzer and gas chromatograph coupled with mass spectrometer（Py-GC/MS）. The main condensable products of xylan pyrolysis consisted of acids, al- dehydes, and ketones; while gas products contained CO2, CO, CH4 and H〉 Acetic acid and furfural were the most abun- dant products with the highest contents of 20.11% and 20.24% respectively. While furfural and acetic acid were formed competitively with residence time and temperature increases, the distribution of xylan pyrolysis products did not vary with the residence time and temperature, while the total content of several kinds of products changed a lot. According to the analysis of experimental data, a reaction pathway of xylan decomposition was deduced so as to illustrate the forma- tion mechanism of main products.